Piloting the integration of SMART Recovery into outpatient alcohol and other drug treatment programs - V. Manning; A. D. Roxburgh; M. Savic (Addiction Science & Clinical Practice, 2023)
Abstract Background Research suggests peer support groups can amplify and extend treatment effects and enhance long-term recovery from Alcohol and Other Drug (AOD) problems. However, they are rarely integrated into outpatient treatment programs, resulting in a missed opportunity for peer-to-peer learning, and increased connection to others social networks where people want to reduce or cease substance use. Method In this mixed-methods study, we examined the uptake, participant experiences and impacts of Self-Management and Recovery Training (SMART) when embedded in three public AOD treatment programs in a pilot program in Australia. Groups were delivered initially in-person but transitioned online during the COVID-19 pandemic. Results A total of 75 SMART Recovery groups were run by the pilot sites, with an average attendance of 6.5 people per meeting. Among Participants (N = 31) who completed the survey, 94% reported benefits relating to substance use (i.e., reduction/ successful maintenance of abstinence), 71% reported improvements in their mental health and wellbeing, 74% reported improvements in their physical health, and 81% reported feeling better connected with others. In-depth qualitative interviews were conducted with 10 participants to explore their experiences. Thematic analysis revealed four themes: motivation to attend, active ingredients, views on the integration of SMART into formal AOD, and the advantages and disadvantages of online groups. Conclusion Taken together, these findings suggest embedding SMART Recovery in AOD treatment is a worthwhile endeavour. This was indicated by a good uptake and evidence of multiple and unique benefits to participants over and above their usual care, notably, better management of their AOD use, health, wellbeing, and sense of connection with others.